An NMR Study on Hydration and Molecular Interaction of Phytantriol-Based Liquid Crystals - Yu Lu; Di Zhu; Quynh Le; Yuji Wang; Wei Wang (MDPI AG, 2022)
Phytantriol-based lyotropic liquid crystals (LLCs) have emerged as a new nanodrug delivery system. However, the understanding of phytantriol-based LLCs is lacking. In this study, we use NMR technology to characterize LLC formation over two months. Three samples in different phases were prepared with different hydration states. NMR data, including 1D-1H, 13C-{1H}, 2D-HSQC, HMBC, COSY, NOESY, etc., were collected. A comprehensive analysis of these NMR data was performed on the three phases of phytantriol-based LLCs. The following results were achieved from the study. First, the 1H and 13C-{1H} spectra of phytantriol were assigned. Second, the change of NMR spectra during the formation of the phases was observed, and the change of hydration was calculated for the time-dependent phase formation. Third, the correlation peaks of 2D-NOESY were used to describe the spatial relationship of lipids-water interaction and lipid-lipid interaction.